(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article investigated the condition of local immunity in the oral cavity in 48 patients with chronic recurrent aphthous stomatitis (CRAS). Patients with CRAS showed a decrease in the level of lysozyme and sIgA in the oral liquid (OL), which is an unfavorable prognostic criterion in patients with CRAS. This undoubtedly affects the course of the pathology in patients with CRAS. Low values of lysozyme and sIgA can lead to impaired microbiocenotic status and reduced functioning of the oral mucosa (OM) in patients with CRAS.